Assessment of neuropharmacological potential of low molecular weight components extracted from Rhinella schneideri toad poison - Baldo, Mateus Amaral (J Venom Anim Toxins Incl Trop Dis, 2019)
BACKGROUND: Studies on toad poison are relevant since they are considered a good source of toxins that act on different biological systems. Among the molecules found in the toad poison, it can be highlighted the cardiotonic heterosides, which have a known mechanism that inhibit Na(+)/K(+)-ATPase enzyme. However, these poisons have many other molecules that may have important biological actions. Therefore, this work evaluated the action of the low molecular weight components from Rhinella schneideri toad poison on Na(+)/K(+)-ATPase and their anticonvulsive and / or neurotoxic effects, in order to detect molecules with actions of biotechnological interest. METHODS: Rhinella schneideri toad (male and female) poison was collected by pressuring their parotoid glands and immediately dried and stored at -20 °C. The poison was dialysed and the water containing the low molecular mass molecules (< 8 kDa) that permeate the dialysis membrane was collected, frozen and lyophilized, resulting in the sample used in the assays, named low molecular weight fraction (LMWF). Na(+)/K(+) ATPase was isolated from rabbit kidneys and enzyme activity assays performed by the quantification of phosphate released due to enzyme activity in the presence of LMWF (1.0; 10; 50 and 100 µg/mL) from Rhinella schneideri poison. Evaluation of the L-Glutamate (L-Glu) excitatory amino acid uptake in brain-cortical synaptosomes of Wistar rats was performed using [3H]L-glutamate and different concentration of LMWF (10(-5) to 10 µg/µL). Anticonvulsant assays were performed using pentylenetetrazole (PTZ) and N-methyl-D-aspartate (NMDA) to induce seizures in Wistar rats (n= 6), which were cannulated in the lateral ventricle and treated with different concentration of LMWF (0.25; 0.5; 1.0; 2.0; 3.0 and 4.0 µg/µL) 15 min prior to the injection of the seizure agent. RESULTS: LMWF induced a concentration-dependent inhibition of Na(+)/K(+)-ATPase (IC(50%) = 107.5 μg/mL). The poison induces an increased uptake of the amino acid L-glutamate in brain-cortical synaptosomes of Wistar rats. This increase in the L-glutamate uptake was observed mainly at the lowest concentrations tested (10(-5) to 10(-2) µg/µL). In addition, this fraction showed a very relevant central neuroprotection on seizures induced by PTZ and NMDA. CONCLUSIONS: LMWF from Rhinella schneideri poison has low molecular weight compounds, which were able to inhibit Na(+)/K(+)-ATPase activity, increase the L-glutamate uptake and reduced seizures induced by PTZ and NMDA. These results showed that LMWF is a rich source of components with biological functions of high medical and scientific interest.